ANALISA DAN PERANCANGAN SISTEM MANAJEMEN KOST BERBASIS ONLINE - Eka Cahya, Septian; Alfa Razaq, Jeffri (Information Technology and Telematics, 2018)
Abstract – The increase in population inflows that every year to the city certainly directly affects the numbers of need for places to live. This is used by entrepreneurs to establish a boarding house with a number of rooms that vary. The problem that is often experienced by entrepreneurs is the unmanaged payment bookkeeping and the neat attention. The purpose of making an 'Online Based Boarding Management Information system' is to be able to help the owner. With this system will produce software that can help users and computer users.